Effectiveness of measuring the mandibular angle and position of the mental foramen for estimating post-mortem human age (Research, Society and Development, 2022)
This research aimed to verify the effectiveness of the prediction of human age when associated with measurements of the location of the mental foramen - FM and measurements of the mandibular angles, using dry jaws, in order to corroborate the possibility of complementary use of this methodology in cases where the mandible is present at the forensic examination. The study was carried out from the records cataloged at the Laboratory of Forensic Anthropology and Osteology - UFPE, and after checking the inclusion and exclusion criteria, it resulted in a sample of 31 mandibles suitable for the study, aged between 17 and 94 years. The mandibular angle and the height of the FM were measured bilaterally, considering the distances from FM to the alveolar ridge, to the base of the mandible and also the height of the mandibular body in its region. The results showed that the methodology presented did not establish statistical significance (p < 0.05), either by relating the numerical variables to age or to the relation of variables against the established age groups (≤ 59 years; ≥ 60 years). Thus, it can be recognized that the association of the measurement of the mandibular angle and the FM position does not have good effectiveness regarding the purpose of age estimation in the studied sample, in view of this, it is recommended to use larger samples in order to offer greater precision in the results and safety in the use of this forensic dentistry method.